Why is There More Crime in Cities? - Glaeser, Edward L.; Sacerdote, Bruce (Journal of Political Economy, 1999)
jba1uJcu1 0j EC0110U! DCbI41JJQIJ1 0, ECOUOUJ!C2 EML r QJ2CL BLIICC 2G1.(101 /AJA ffJQ2C CJJL9C1CU2PC2 91.G C0UUQC1G 114 ff1 flLJ I!A!IJ gIG rapii CL!UJG bLcunnw 12 22oc1cq 1141JJ IJJG2G CIWLC1GL!2ffC2' Pill IItG 9LG jG lIAIU 10 cxbprni ffLG ffJO2G 1JJ1 LGUGCI W21C2 20C!9j !UUflGUCG2 uq jIUJ!JX 2PJICWLC flJ1UJ11C1Ae MG C1J 2A gI1 02CLAjC CPI2C1CL!2ffC2 0 Uq14qnJ2 uq C!ffG2 BIG CJJLC1GI42ffC2 1JJ1 2GCUJ 111021 !UJb0L1U1 1 W021 5 01 gIG ntpu CI4UJC GGC1 BIG LGUJUTU f-Q1) 0 gIG GUCCI CIJ pG LG!1G 10 uq JoNci. bLoppJiX 04 LGC0Uff 01? LG GgU1IG 0 1n.pu I11G fl1 1J1G2G C10L2 2CCUI 10 cxbjnu CUJG C0IJ1JCC10IJ jOL U0U-bGCflhJ!LX CL!UJG2 2flC 2 LbG OL 22U1J1 0MGL